2015
DOI: 10.1093/jac/dkv322
|View full text |Cite
|
Sign up to set email alerts
|

NLF20: an antimicrobial peptide with therapeutic potential against invasivePseudomonas aeruginosainfection

Abstract: Together, these results indicate that functional epitopes of HCII may have therapeutic potential against bacterial infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(15 citation statements)
references
References 50 publications
0
15
0
Order By: Relevance
“…HCII belongs to the serpin family that has increasingly been shown to have non-inhibitory roles in inflammation and angiogenesis. 10,15,46 Therefore it is also possible that HCII-N also may have a non-inhibitory role.…”
Section: Discussionmentioning
confidence: 99%
“…HCII belongs to the serpin family that has increasingly been shown to have non-inhibitory roles in inflammation and angiogenesis. 10,15,46 Therefore it is also possible that HCII-N also may have a non-inhibitory role.…”
Section: Discussionmentioning
confidence: 99%
“…Upon its interaction with cell surface glycosaminoglycans, the inert HCII undergoes conformational changes that activate it and induce novel biological functions, including endotoxin binding and antimicrobial properties (45,46). Peptide epitope mapping localized the antimicrobial properties of HCII to helices A and D (45,47). In vivo analysis revealed that HCII-deficient mice were more susceptible to P. aeruginosa infection than their wild-type counterparts, while challenge of wild-type mice with P. aeruginosa reduced the level of HCII within their bodies (45).…”
Section: Discussionmentioning
confidence: 99%
“…In vivo analysis revealed that HCII-deficient mice were more susceptible to P. aeruginosa infection than their wild-type counterparts, while challenge of wild-type mice with P. aeruginosa reduced the level of HCII within their bodies (45). Using a murine model of P. aeruginosa sepsis, Papareddy et al (47) demonstrated that intraperitoneal injection of mice with synthetic NFL20, a peptide that corresponds to the D helix of HCII, significantly enhanced their survival. Additionally, the number of P. aeruginosa bacteria recovered from the liver, kidney, and spleen of NLF20-treated mice was significantly reduced compared with the number recovered from those organs of untreated infected mice (47).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This example of additive cooperation of AMPs provides valuable information for considering future therapeutic strategies regarding the combination of AMPs. Notably, the therapeutic efficacy of AMPs was evaluated in the clinical context not only for their direct antibacterial activity, but also the indirect immunomodulatory activity to promote the clearance of bacterial infection [3,12]. The aims of this study were to compare the antibacterial and antibiofilm activities of the four cathelicidins BMAP-27, BMAP-34, mCRAMP, and LL-37, to determine their immunomodulatory activity on neutrophils, and to evaluate the therapeutic efficacy of the combination of BMAP-27 and LL-37 against P. aeruginosa infection.…”
Section: Introductionmentioning
confidence: 99%